2012
DOI: 10.1007/s10194-012-0493-y
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities and self-reported depression in a sample of patients with chronic headache

Abstract: White matter hyperintensities (WMH) have been associated with mood disorders in psychiatric patients. In the present study, we aimed to assess whether WMHs are associated with depressive symptoms and different sensitivity of the behavioral inhibition (BIS), and activation (BAS) systems in patients with chronic headache. Participants were 85 adult outpatients (16 men and 69 women) with a diagnosis of chronic headache. All of the patients underwent brain magnetic resonance imaging (MRI) and were administered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
(56 reference statements)
0
14
1
Order By: Relevance
“…These data are in line with some previous literature [26,37-39], indicating that the most common psychiatric conditions related to migraine were depression, bipolar disorders, anxiety [19] and somatoform disorders. However, the relationship between CDH and psychiatric disorders is still matter of debate in the literature, this being also due to the different headache diagnostic criteria and the different methods adopted in most of the studies to assess psychiatric disorders [12-16]. Verri and colleagues [21] found an association between CDH and at least one psychiatric disorder in 90% of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are in line with some previous literature [26,37-39], indicating that the most common psychiatric conditions related to migraine were depression, bipolar disorders, anxiety [19] and somatoform disorders. However, the relationship between CDH and psychiatric disorders is still matter of debate in the literature, this being also due to the different headache diagnostic criteria and the different methods adopted in most of the studies to assess psychiatric disorders [12-16]. Verri and colleagues [21] found an association between CDH and at least one psychiatric disorder in 90% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying risk factors for progression has emerged as a major public health priority. Psychiatric comorbidity has been one of the risk factors most widely investigated for headache chronification due the significant role it may play in this process [12-16] and because it might be linked to medication overuse in migraineurs [17]. Many epidemiological and clinical studies have confirmed the elevated risk for mood and anxiety disorders in migraine and in CDH [18-23].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Diagnostic criteria for diagnosing this disease include normal initial psychomotor development, deterioration following infection or trauma, presence of ataxia and spasticity with MR features of diffuse white matter signal changes with signal intensity of CSF on all pulse sequences. 15,16,17 Additional features are lesions in central tegmental tracts and basis pontis. Subcortical white matter involvement is early and severe.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors suggest WMH may play a role in the development of mood disorders, others report no association between WMH and depressive symptoms [24,25,26,27,28,29]. When dealing with stroke patients, no relation between post-stroke depressive symptoms and pre-existing WMH in the brain could be ascertained [26,29,30].…”
Section: Discussionmentioning
confidence: 99%